2018
DOI: 10.1080/1828051x.2018.1501283
|View full text |Cite
|
Sign up to set email alerts
|

Hematobiochemical profiles, mineral concentrations and oxidative stress indicators in beef cattle with pica

Abstract: Pica, or "depraved appetite", is defined as ingestion of non-nutritive substances. Many factors influencing pica in animals have been identified , but the etiology is controversial. This study was conducted to evaluate haematological and biochemical parameters, trace element concentrations, the total antioxidant status (TAS), total oxidative status (TOS) and oxidative stress index (OSI) in beef cattle with and without pica. Ten beef cattle with pica (group I) and another ten healthy beef cattle (Group II) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 13 publications
7
8
0
Order By: Relevance
“…Some studies (4,10,20) found an increase in the serum CRE concentration, whereas others reported reduced levels of CRE (3,9,25). An increase in LDH levels has also been reported (1,9,25). The changes in serum AST, ALT, LDH and GLU levels in the present study are consistent with the findings of the other studies (3,4,9,10,20,25).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Some studies (4,10,20) found an increase in the serum CRE concentration, whereas others reported reduced levels of CRE (3,9,25). An increase in LDH levels has also been reported (1,9,25). The changes in serum AST, ALT, LDH and GLU levels in the present study are consistent with the findings of the other studies (3,4,9,10,20,25).…”
Section: Resultssupporting
confidence: 90%
“…An increase in LDH levels has also been reported (1,9,25). The changes in serum AST, ALT, LDH and GLU levels in the present study are consistent with the findings of the other studies (3,4,9,10,20,25). The decreased CRE level was consistent with the findings of some of the abovementioned studies (3,9,25), but inconsistent with the findings of some others (4,10,20).…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations